Alexander and Demaratus of Corinth at the Battle of the River Granicus - Sekunda, Nicholas Victor (Anabasis. Studia Classica et Orientalia, 2018)
The concept Peter Green first suggested in 1974 that the battle of the River Granicus in 334 BC was a two phase battle, with an unsuccessful cavalry charge across the river on the afternoon of the first day, followed by a night march crossing the river, with a successful battle on the second day, should be revived. Demaratus of Corinth is attested at Granicus in fighting at the side of Alexander of Macedon. A few years earlier, at the battle of the River Damurias in Sicily, he was very probably a witness to a charge across a steep-banked river, against Greek mercenary opponents by the cavalry of Timoleon. Probably, the idea that a cavalry charge across the river against Granicus against a formation of hoplites, could have been successful was suggested to Alexander by Demaratus of Corinth.